2017
DOI: 10.1007/s00181-017-1308-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of workplace learning in higher education on employment and match quality: is there an early-career trade-off?

Abstract: We investigate whether the choice for a higher education program with a substantial workplace learning component entails an early-career trade-off between on the one hand higher employment chances and better initial matches (when opting for a program with workplace learning) and on the other hand a lower risk of bad match persistence (when opting for a program without workplace learning). To this end, we rely on longitudinal data of Belgian graduates that track their careers up until the age of 29. We model th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
1
13
0
1
Order By: Relevance
“…Alternatively, vocational programmes that combine a less-specific focus with workplace learning seem to be less effective in terms of avoiding overeducation and overskilling. This conclusion aligns with those of Verhaest and Baert (2017). When differentiating between vocational and general programmes in higher education on the basis of the presence of curriculum-based work placement, they did not find clear effects either.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Alternatively, vocational programmes that combine a less-specific focus with workplace learning seem to be less effective in terms of avoiding overeducation and overskilling. This conclusion aligns with those of Verhaest and Baert (2017). When differentiating between vocational and general programmes in higher education on the basis of the presence of curriculum-based work placement, they did not find clear effects either.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, some research also indicated that these overqualified vocationally educated individuals acquire less additional skills than overqualified generally educated individuals (Verhaest and Omey, 2013). While all of this is supportive for a trade-off between the short-run and long-run effects on educational mismatches, a recent contribution by Verhaest and Baert (2017) did not find any evidence on differences between graduates with and without curriculum-based workplacement experience in their likelihood to be overeducated in the first job, nor in the likelihood to remain overeducated.…”
Section: Introductionmentioning
confidence: 98%
“…There have been debates for decades on whether the focus on policy should be on vocational or core education (Arum & Shavit, 1995; Giret, 2011; Hanushek, Schwerdt, Woessmann, & Zhang, 2017; Heijke, Meng, & Ris, 2003; Verhaest & Baert, 2017). According to Verhaest and Baert (2017), TVET has long been praised for its success in advancing school-to-work transitions and reducing youth unemployment.…”
Section: The Background and Contextmentioning
confidence: 99%
“…There have been debates for decades on whether the focus on policy should be on vocational or core education (Arum & Shavit, 1995; Giret, 2011; Hanushek, Schwerdt, Woessmann, & Zhang, 2017; Heijke, Meng, & Ris, 2003; Verhaest & Baert, 2017). According to Verhaest and Baert (2017), TVET has long been praised for its success in advancing school-to-work transitions and reducing youth unemployment. However, some scholars argue that the long-term effects could be negative (Goldin, 2001; Krueger & Kumar, 2004), as vocational skills are strongly tied to a specific context and there is the risk of skills becoming obsolete (Verhaest & Baert, 2017).…”
Section: The Background and Contextmentioning
confidence: 99%
“…The earnings differences we calculate therefore can be interpreted as causal effects of differences in the choice of the education path. So far, most comparisons of the returns to education of vocational and academic education are on secondary education or they do not take into account differences in the prestige and selectivity of vocational and academic education (Verhaest and Baert 2018).…”
Section: Introductionmentioning
confidence: 99%